Auriculotherapy in the control of anxiety symptoms in health personnel: a systematic review (Research, Society and Development, 2021)
Anxiety is a common problem among health professionals, however, few studies investigate non-pharmacological methods such as auriculotherapy for its control. The aim of the study was to carry out a systematic review of the effectiveness of auriculotherapy in the control of anxiety symptoms in healthcare professionals. The recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-analyses 2020 (PRISMA 2020) were followed. Randomized controlled trials in Portuguese, English and Spanish were included, without restriction of year of publication, registered in the MEDLINE/PubMed, Bireme, Scopus, Embase, CENTRAL (Cochrane Library) and Academic Google databases. Of the 213 records found, one clinical trial carried out in Brazil was included in the final analysis. The results showed that auriculotherapy reduced anxiety symptoms by 17% in the group treated with needles, 13% with seeds and 11% with adhesive tape. Thus, although auriculotherapy has contributed to the control of anxiety symptoms in health professionals, evidence is scarce.